Эпитафия скифского царя Аргота - Сидоренко, В.А. (Материалы по археологии, истории и этнографии Таврии, 2005)
При раскопках на городище Неаполя Скифского вблизи от городских ворот в 1999 гг. были найдены фрагменты известняковой плиты с греческим текстом, части которого сохранились более чем на пятидесяти обломках камня и были соединены в восьмистрочную надпись, представлявшую собой метрическую эпитафию. После предварительной публикации [Виноградов, Зайцев 2003, с. 44-53] надпись опубликована ее находчиком Ю.П.Зайцевым [Зайцев 2003, с.52, рис. 37, 1,40-41] почти без изменений. In 1999, during the excavations of Neapolis Scythian (in Crimea), near the town gate a number of debris of the lime slab with poetical Greek inscription were found. The translation and reconstruction of parts of this inscription were published in a preliminary publication by the Yu. G. Vinogradov and Yu. P. Zaitcev [The new epigraphy antiquity from Scythian Naples (preliminary publication) // Archaeology, 2003, n. 1, Kyev, p, 44-53 (in Ukrainian)], and only by Yu. P. Zaitcev [Neapolis Scythian (II Century B.C.- III Century A.D.). Simferopol, 2003, p. 52, pages 37, f; 40-41 (in Russian)]. In their opinion the memorial was founding by Scythian king Scilur, whose name is not mentioned in the inscription. The epitaph gives interesting information on famous king Argot, but the historical reconstruction of interrelations between Argot and Scilur is not motivated. Wrongly restored in the end of first line a verbal είστησεν] in the literal sense was transferred inscription to building category. The authors by mistake join for restore text two heterogeneous fragments from excavations in 1950. Restored parts of the text contain hiatus, sometimes is not commensurable with blank in stone. In article the author proposes redacted reading with partial restore and translation of the poetical epitaph.